The Role of Bawaslu in Upholding Election Justice through Process Dispute Resolution in the 2024 Boalemo Regional Election - Panigoro, Yesmar; Lahaling, Hijrah; Rusmulyadi (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
Independent candidacy in local head elections constitutes an important instrument for expanding political participation at the local level; however, in practice, it frequently gives rise to administrative disputes that directly affect the fulfillment of citizens’ political rights. This study aims to analyze the resolution of disputes involving independent candidates in the 2024 Regional Head Election (Pilkada) of Boalemo Regency and to assess the role of the Election Supervisory Body (Bawaslu) in realizing electoral justice. The research employs a normative juridical method, using statutory, conceptual, and case study approaches focused on two independent candidacy disputes handled by the Boalemo Regency Bawaslu. The findings indicate that the disputes were primarily triggered by inconsistencies between support data recorded in the digital nomination system (SILON) and physical supporting documents, as well as procedural limitations in the verification process. Bawaslu functioned not merely as an enforcer of legal certainty but also as a corrective institution that safeguards political rights through adjudicative decisions and deliberative (musyawarah) mechanisms. The dispute resolution practices reflect a balanced application of procedural and substantive justice. This study concludes that strengthening institutional capacity, integrating electoral information systems, and optimizing non-litigation dispute resolution mechanisms are essential prerequisites for achieving electoral justice and enhancing the quality of local democracy.